1999
DOI: 10.1046/j.1365-2567.1999.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of parasite‐specific immunoglobulin G by purified blood B lymphocytes from immune individuals after in vitro stimulation with recombinant Plasmodium falciparum merozoite surface protein‐119 antigen

Abstract: The C-terminal 19 000 MW fragment of merozoite surface protein-1 (MSP119) is one of the most promising candidate antigens for a malaria vaccine. Baculovirus recombinant Plasmodium falciparum MSP119 has been used to define conditions for the in vitro production of specific antibodies by purified human blood B cells in a culture system where T-cell signals were provided by the engagement of CD40 molecules and exogenous cytokines. MSP119 preferentially induced surface immunoglobulin G (IgG) -positive (sgamma+) B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 31 publications
4
22
0
Order By: Relevance
“…Production of anti-P. falciparum Ab in vitro required T-cell-derived signals, such as IL-2 plus IL-10 (or IL-4), in agreement with studies of other systems (17,19,20,22). We have shown that B cells from donors exposed to malaria, but not B cells from donors who are not exposed to malaria, can be reactivated in vitro to secrete malaria-specific Abs and that for many individuals the pattern of in vitro Ab production mirrors the pattern of circulating Ab in the plasma.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Production of anti-P. falciparum Ab in vitro required T-cell-derived signals, such as IL-2 plus IL-10 (or IL-4), in agreement with studies of other systems (17,19,20,22). We have shown that B cells from donors exposed to malaria, but not B cells from donors who are not exposed to malaria, can be reactivated in vitro to secrete malaria-specific Abs and that for many individuals the pattern of in vitro Ab production mirrors the pattern of circulating Ab in the plasma.…”
Section: Discussionsupporting
confidence: 82%
“…Culture supernatants were recovered and tested for polyclonal or Ag-specific IgGs by ELISA as described previously (17,19,39). Polyclonal peroxidaseconjugated goat anti-human IgGs were obtained from Cappel-Organon Technika, (Turnhout, Belgium) and used at the following dilutions: total IgG, 1:6,000; IgG1, 1:2,000; IgG2, 1:10,000; IgG3, 1:10,000; and IgG4, 1:30,000.…”
Section: Methodsmentioning
confidence: 99%
“…The identification of P. falciparum-derived products and of the mechanisms responsible for B-cell activation has remained elu- sive though direct and indirect mechanisms mediated by T cells and accessory cells have been proposed to explain this phenomenon (9,12,16,19). Here we show that CIDR1␣ directly activates in vitro purified B cells from nonimmune donors and binds to various Ig fragments and to Igs from different species and, therefore, could be defined as a superantigen.…”
Section: Discussionmentioning
confidence: 76%
“…mAbs to MSP-1 have been found to inhibit in vitro growth of parasites (33,34). Ab levels to MSP-1 19 correlate with age-related changes in the level of asexual parasitemia in some, but not all malaria endemic areas (35)(36)(37)(38)(39)(40)(41). Primate vaccine trials (42,43) and studies of mouse malaria models indicate that immunization with MSP-1 19 (44,45) protects against blood-stage infection.…”
Section: Discussionmentioning
confidence: 99%